AIRPORT PLAN TOPOGRAPHIC EXAMINATION: ACCURACY ANALYSIS BY DEMNAS AND ASTER GDEM METHOD IN TERRESTRIAL SURVEYS - Soraya Irene; Pintanugra Persadanta; Willy Adrian (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Penerbangan Palembang, 2023)
An airport feasibility study is an important thing that must be completed to propose a new airport as a condition for issuing an airport location determination. The most critical indicator is the technical construction, which examines the topographic conditions of the new airport location. The topographic conditions using a terrestrial survey are highly accurate because they are carried out directly on the analyzed object. However, terrestrial surveys require time, energy, and money. This study aims to examine the topographic conditions using DEMNAS and ASTER GDEM, which can provide the same data as terrestrial surveys with a spatial resolution of 8 meters and 30 meters for free. The results of the comparative analysis show that the average elevation difference between DEMNAS and ASTER GDEM against terrestrial survey in the new airport location plan in Mahakam Ulu Regency is 2.04 meters and 8.89 meters, respectively. The validity and accuracy test of DEMNAS against terrestrial survey resulted in R2 0.963, RMSE 2.417 meters, NSE 0.941, and LE90 3.897 meters. ASTER GDEM against terrestrial survey resulted in R2 0.674, RMSE 6.244 meters, NSE -0.666 and LE90 10.3 meters. The analysis results show that DEMNAS data is better than ASTER GDEM. The conclusion is that DEMNAS data has a good level of accuracy that can be used to determine and analyze the topographic conditions of the new airport land plan so that it can be an alternative for the initiator in preparing the airport feasibility study.